The Secrecy Heuristic: Inferring Quality from Secrecy in Foreign Policy Contexts. Issue 1 (12th June 2013) - Travers, Mark; Van Boven, Leaf; Judd, Charles
<x xml:space="preserve">Abstract</x> Three experiments demonstrate that in the context of U.S. foreign policy decision making, people infer informational quality from secrecy. In Experiment 1, people weighed secret information more heavily than public information when making recommendations about foreign political candidates. In Experiment 2, people judged information presented in documents ostensibly produced by the Department of State and the National Security Council as being of relatively higher quality when those documents were secret rather than public. Finally, in Experiment 3, people judged a National Security Council document as being of higher quality when presented as a secret document rather than a public document and evaluated others' decisions more favorably when those decisions were based on secret information. Discussion centers on the mediators, moderators, and broader implications of this secrecy heuristic in foreign policy contexts.